Evaluation of the Antibacterial Activity of Acetic Acid in Comparison With Three Disinfectants Against Bacteria Isolated From Hospital High-Touch Surfaces - Ayesha Muazzam; Sidrah Saleem; Hafiz Muhammad Faizan Nadem; Faiz Ul Haq; Ghaniya Ali; Nida Javed (Scientifica)
Acetic acid, a readily available and less toxic alternative to conventional disinfectants, is widely used for cleaning in household settings. This study evaluates the antibacterial efficacy of acetic acid against bacteria isolated from hospital high-touch surfaces, comparing its performance to commonly used disinfectants, including phenol, sodium hypochlorite, and didecyldimethylammonium chloride (DDAC). A total of 120 samples were collected from high-touch surfaces in specialized patient areas. The antibacterial activity of acetic acid, phenol, sodium hypochlorite, and DDAC was assessed using the standard broth microdilution method against the isolated bacterial strains. From the 120 samples, 140 bacterial isolates were obtained. Acetic acid demonstrated strong antibacterial activity, with mean minimum inhibitory concentrations (MICs) ranging from 0.05 ± 0.00 to 0.25 ± 0.06 μL/mL, effectively inhibiting coagulase-negative Staphylococcus (CONS), Klebsiella pneumoniae, Proteus vulgaris, Enterococcus species, and Serratia marcescens. Its performance surpassed phenol and DDAC against these strains. Phenol exhibited higher MICs (0.50 ± 0.00 to 0.83 ± 0.10 μL/mL), indicating lower efficacy, while DDAC (0.06 ± 0.00 to 0.17 ± 0.04 μL/mL) and sodium hypochlorite (0.06 ± 0.00 to 0.10 ± 0.00 μL/mL) demonstrated comparable antibacterial effects. Phenol and sodium hypochlorite were found nonsignificant, while DDAC is highly effective at a concentration of 8.5%. Hospital surfaces were found to be contaminated with diverse bacterial strains. Acetic acid demonstrated significant antibacterial efficacy against both gram-positive and gram-negative bacteria, with MICs ranging from 0.05 ± 0.00 to 0.25 ± 0.06 μL/mL, suggesting its potential as an effective, economical, and less toxic alternative to conventional disinfectants.